Inflation expectations and energy price forecasting - Baghestani, Hamid (2014)
In this study, we ask whether US consumers' inflation expectations provide useful information for accurately predicting the direction of change in energy prices. As such, we set up a forecasting model to generate the one-, two- and three-quarter-ahead random walk forecasts of crude oil, gasoline and heating oil prices. For the period 1987–2012, our test results reveal that the forecasts are free of systematic bias and thus imply symmetric loss. Also, they are generally efficient, where efficiency means the forecast error is uncorrelated with its own past values. The random walk forecast errors are, however, correlated with the change in inflation expectations (measured by the data from the Michigan Surveys of Consumers). Thus, we conclude such expectations may contain useful predictive information for crude oil, gasoline and heating oil prices. Consistent with this conclusion, we show that the change in inflation expectations accurately predicts the direction of change in such energy prices for 1987–2012.